La redistribución del gasto publico y su incidencia en la estructura presupuestaria del gobierno autónomo descentralizado del cantón EL Empalme, periodo 2010-2014 - Palacios Thomson, Carlos Enrique (2016)
The present research on "REDISTRIBUTION OF PUBLIC SPENDING AND ITS IMPACT ON THE BUDGET STRUCTURE OF THE HOME GOVERNMENT decentralized El Empalme Canton, PERIOD 2010-2014" is a priority to identify administrative operations in which activities contribute revenues are made economic and financial resources for the implementation of works that benefit the canton. The respective references, theories and economic models, plus the redistribution of public spending, the budget amount, satisfaction of the people, economic resources, therefore the administrative operations and economic activities are based, these variables contributed to the development expand knowledge through books, documents, magazines and scientific articles. It states that the local government of the Autonomous Decentralized Government Canton El Empalme is the cornerstone for the implementation of the annual budget amount, underestimated these values is not enough to achieve works undertaken in the most vulnerable sectors causing discomfort to the general public. Officials need to contribute to the strengthening of the internal administration of the municipality, strategies should be encouraged to enter the municipal coffers tax revenues and taxpayers meet their obligations generating greater economic value in the budget amount managing to reach reach several works sectors. Keywords: redistribution, government spending, budget structure municipality.